2015
DOI: 10.1021/acs.joc.5b00544
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ring Size and Polar Functional Groups on the Glutathione Peroxidase-Like Antioxidant Activity of Water-Soluble Cyclic Selenides

Abstract: To elucidate the effects of ring structure and a substituent on the glutathione peroxidase- (GPx-) like antioxidant activities of aliphatic selenides, series of water-soluble cyclic selenides with variable ring size and polar functional groups were synthesized, and their antioxidant activities were evaluated by NADPH-coupled assay using H2O2 and glutathione (GSH) in water and also by NMR spectroscopy using H2O2 and dithiothreitol (DTT(red)) in methanol. Strong correlations were found among the GPx-like activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…[51] While several of the cyclic seleninates and spiroselenuranes describeda bove have improveda ctivity compared to ebselen in the indicated assays,m ost display equally poor solubility in water.I no rder to improves olubility,s elenides 36 and 38 were prepared, representing the reduced form of spiroselenuranes 37 and 39,r espectively. [52,53] These compounds retain one arylseleniumb ond in order to resist metabolic conversion into toxic inorganic species, but display much improved solubility properties. Thus, selenides 36 proved soluble in 5% ethanolwater,w hile the additional hydroxyl group in compounds 38 renderedt hem freely soluble in water alone.…”
Section: Spirodioxyselenuranesmentioning
confidence: 99%
“…[51] While several of the cyclic seleninates and spiroselenuranes describeda bove have improveda ctivity compared to ebselen in the indicated assays,m ost display equally poor solubility in water.I no rder to improves olubility,s elenides 36 and 38 were prepared, representing the reduced form of spiroselenuranes 37 and 39,r espectively. [52,53] These compounds retain one arylseleniumb ond in order to resist metabolic conversion into toxic inorganic species, but display much improved solubility properties. Thus, selenides 36 proved soluble in 5% ethanolwater,w hile the additional hydroxyl group in compounds 38 renderedt hem freely soluble in water alone.…”
Section: Spirodioxyselenuranesmentioning
confidence: 99%
“…[7b] However, such structural modifications of the simple Se-containing cyclic compounds have not been readily achieved in practical organic synthesis. [8] In addition, we have recently reported that selenenyl sulfide (SeÀ S) analogues of 1, which is a model compound of the thioredoxin reductase active center composed of C497 and selenocysteine (U) 498, catalyzes the reduction of H 2 O 2 , a reactive oxygen species, and protein SS bonds in the presence of a dithiol activator. [9] This model study revealed that neighboring His472 at the active center kinetically accelerates the reduction of the SeÀ S bond between C497 and U498, and thermodynamically stabilizes the generated reactive selenolate (Se À ) state by forming intramolecular NH *** Se hydrogen bond.…”
Section: Introductionmentioning
confidence: 99%
“…13 Similar activities were presented by a camphor based selenamide derivative 14 and some water soluble selenides, presenting different ring sizes and organic chemical functionality classes. 15 Organoselenium compounds which act against lipid peroxidation, free radical chain reaction 16 and possess pharmacological properties have been extensively investigated. 17,18 In fact, the hypohalous acid-scavenging efficiency of some synthetic selenium-containing compounds, including selenomethionine, has been described.…”
Section: Introductionmentioning
confidence: 99%